La comunicación estratégica del Consejo Nacional Electoral de Los Ríos previo a las elecciones seccionales - Apraez Montero, Dayanna Gibelly (2023)
The present investigation regarding the strategic communication of the National Electoral Council of Los Ríos, prior to the sectoral elections, aims to analyze a wide variable, but of great importance, such as communication. The study details the need to know the communication processes of the public entity, since its primary work is related to announcing to the citizens of Rio de Janeiro everything related to sectoral elections; Therefore, the exposed theme is considered relevant, since when the decisions of a country play a fundamental role, it is necessary that the transmission of the obligations and rights of Ecuadorians be described and communicated in a timely manner. Strategic communication in simple words is defined as the design of plans and tools correctly applied to generate a positive link between the company and a group of interest, not only in the commercial private sector, but also by public entities, since Their work is linked to satisfying the people's need for information. The method used to obtain truthful and relevant results to the investigation is analytical, due to the nature of the investigation that requires issuing solid conclusions from the study findings. Research that concludes with the importance of strategic communication within the CNE Los Ríos; In addition, new strategies must be implemented that have an impact on society and enhance the institutional image.